Tomographic Analysis of Jammed Ellipsoid Packings - Schröter, Matthias; Schaller, Fabian; Neudecker, Max; Saadatfar, Mohammad; Delaney, Gary; Mecke, Klaus; Schröder-Turk, Gerd (American Institute of Physics, 2013)
Disordered packings of ellipsoidal particles are an important model for disordered granular matter. Here we report a way to determine the average contact number of ellipsoid packings from tomographic analysis. Tomographic images of jammed ellipsoid packings prepared by vertical shaking of loose configurations are recorded and the positions and orientations of the ellipsoids are reconstructed. The average contact number can be extracted from a contact number scaling (CNS) function. The size of the particles, that may vary due to production inaccuracies, can also be determined by this method.
Keywords: Granular matter; Ellipsoids; Tomography; Contact numbers